2015
DOI: 10.1007/s00431-015-2604-7
|View full text |Cite
|
Sign up to set email alerts
|

Early menarche is associated with metabolic syndrome and insulin resistance in premenopausal Korean women

Abstract: Early menarche (<12 years) is associated with metabolic syndrome and insulin resistance in nationally representative Korean premenopausal women. However, late menarche (>16 years) is not associated with metabolic syndrome after controlling for age and other confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 33 publications
3
34
2
Order By: Relevance
“…This cutoff is about to be similar with that used for definition of early menarche in previous studies reporting its association with metabolic syndrome [3456]. To best of our knowledge, this is the first time to define a cutoff for age at menarche that predicts metabolic syndrome using ROC curve analysis.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This cutoff is about to be similar with that used for definition of early menarche in previous studies reporting its association with metabolic syndrome [3456]. To best of our knowledge, this is the first time to define a cutoff for age at menarche that predicts metabolic syndrome using ROC curve analysis.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies showed a link between early age at menarche and increased risk of metabolic syndrome [3456]. However, the definition of early menarche at these studies either below 12 years [345] or below 12.5 years [6] was based on background data in their communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, postmenopausal women possibly still benefit from the endogenous estrogen produced during their reproductive history, due to the effects it would have exerted on conventional cardiovascular risk factors . Among female reproductive factors, early menarche and early menopause have been identified to be associated with the risk of mortality from cardiometabolic disease in postmenopausal women . Nevertheless, there is still little knowledge about whether the duration of the reproductive lifespan could have a role in MetS risk after menopause.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that there was a negative relationship between BMI and menarche age in a cohort study [25] and early menarche was associated with increased adult BMI in a meta-analysis [26]. Data have consistently shown that women with early menarche have higher risks of metabolic syndrome, type 2 diabetes and cardiovascular disease [252728]. Conversely, in our study, subjects with menstrual irregularity had a higher age of menarche (14.0±0.1) compared to subjects without menstrual irregularity (13.8±0.0).…”
Section: Discussionmentioning
confidence: 99%